Cross helicity of magnetic clouds observed by Parker Solar Probe - Good,S; Kilpua,E; Ala-Lahti,M; Osmane,A; Bale,S; Zhao,L (2021)
Magnetic clouds are large-scale transient structures in the solar wind with low plasma β, low-amplitude magnetic field fluctuations, and twisted field lines with both ends often connected to the Sun. We analyse the normalised cross helicity, σc, and residual energy, σr, in magnetic clouds observed by Parker Solar Probe (PSP). In the November 2018 cloud observed at 0.25 au, a low value of σc was present in the cloud core, indicating that wave power parallel and anti-parallel to the mean field was approximately balanced, while the cloud’s outer layers displayed larger amplitude Alfvénic fluctuations with high σc values and σr ~ 0. These properties are compared and contrasted to those found in clouds observed by PSP at larger heliocentric distances. We suggest that low σc is likely a common feature of magnetic clouds given their typically closed field structure, in contrast to the generally higher σc found on the open field lines of the solar wind.</p&amp